PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN TEKNIK PETA PIKIRAN (MIND MAPPING) UNTUK MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL PECAHAN DI KELAS VII SMP NEGERI 14 JEMBER SEMESTER GANJIL TAHUN AJARAN 2013/2014 - Tyas, Rini Ayuning; Suharto, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2015)
Abstract. There are many students who have difficulty in solving math problems. The difficulties caused students mistake in solving problems. The of student’s mistakes consist of the use of computation errors, errors due to a lack of basic knowledge, reduction errors, and another errors. Therefore, the aplication of cooperative learning model with Mind Mapping technic is important to overcome the student’s mistakes in solving the Fraction problems at seven grade SMP Negeri 14 Jember odd semester academic year 2013/2014. This research type is a Classroom Action Research (CAR). The data analysed in this research are student’s activity, student’s mistakes, and effectiveness. The research show that student’s activity attain 66,48% in the first cycle and 71,62% in second cycle, student’s mistakes attain 50,72% in the first cycle and 34,28% in second cycle, and effectiveness attain 33,64% in the first and 60,67% in the second . It can be concluded that the application of cooperative learning model with Mind Mapping technic is effective to overcome student’s mistakes in solving Fraction. Key Words: Cooperative learning model with Mind Mapping technic, fraction, student’s activity, student’s mistakes, effectiveness